PERBEDAAN PENGARUH PENGGUNAAN ALAT KONTRASEPSI IUD DAN SUNTIK TERHADAP SIKLUS HAID PEREMPUAN DI KECAMATAN MARPOYAN DAMAI PEKANBARU - Ikhwani Ratna; Irdayanti Irdayanti (Marwah: Jurnal Perempuan, Agama dan Jender, 2012)
This study aims to determine the difference of the menstrual cycle between the user of IUD contraception and the inject contraception and to know the side effects of these two devices towards the women in Marpoyan Damai the District, Pekanbaru. The population of this study is all the new users of IUD and inject contraception in Merpoyan Damai disctrikck, Pekanbaru, from January to March 2012, 69 women are using IUD and 564 women using injection. This study is non-experimental descriptive analytic cross sectional approach and Slovin technique is used for taking the sample. Data is analyzed using by statistical techniques to an independent t-test. The results suggest P is 0.006 with significantly less than 0.05, it means that there is a significant differences between menstrual cycles of women who used the IUD contraception and who usess injection contraception.